Social Design : Gestalten fur die Transformation der Gesellschaft - Banz, Claudia (Design ;, 2016)
Is it possible to transform society through design? What possibilities do designers possess, and what responsibilities do they bear? How do understandings of design contents and tasks change, and what does the occupation of a social designer look like? This book looks into these and other questions. From cross-disciplinary perspectives, the contributions offer a complex insight into the history and practice of social design, investigates its socio-cultural relevance and looks into its transformative potential.